Lampung Customary Culture as the Foundation of Social Development: Perspective of Community Empowerment and Welfare - Rika Damayanti; Imanudin Imanudin (Empower : Jurnal Pengembangan Masyarakat Islam, 2024)
The purpose of this study is to analyze the role of Lampung cultural customs so that they can be optimized as a foundation in social development efforts, especially from the perspective of community empowerment and welfare. The research method used is descriptive qualitative with a case study approach, the data used are interviews and direct observation of community leaders and traditional leaders. Data analysis adopts from Robert Yin by making an explanation, which includes (1) making a theoretical statement/initial proposition about social policy/behavior; (2) comparing initial case findings with statements/propositions; (3) improving statements; (4) comparing improvements with existing facts; (5) repeating the process as many times as necessary. The results of the study indicate that cultural values such as mutual cooperation and local wisdom in the form of sekura parties contribute significantly to strengthening social solidarity and community participation in the development process. In addition, the integration of cultural customs in empowerment programs can improve the economic and social welfare of the community. These findings emphasize the need for collaboration between the government, community, and related institutions to ensure that cultural values remain relevant in facing modern challenges